Study on Immune Response of Organs of Epinephelus coioides and Carassius auratus After Immersion Vaccination With Inactivated Vibrio harveyi Vaccine - Gong, Hua; Wang, Qing; Lai, Yingtiao; Zhao, Changchen; Sun, Chenwen; Chen, Zonghui; Tao, Jiafa; Huang, Zhibin (Frontiers in Immunology, 2021)
Immersion vaccination relies on the response of fish mucosa-associated lymphoid tissues, the Crucian carp (Carassius auratus) and Grouper (Epinephelus coioides) were researched in this paper to examine local mucosal immune responses and associated humoral system responses following immersion vaccination. We administered 1.5×107 CFU/mL formalin-inactivated Vibrio harveyi cells and measured mucus and serum antibody titers as well as IgM, MHCⅡ mRNA levels in immune organs. The mucosal antibody response preceded the serum response indicating a role for local mucosal immunity in immersion vaccination. IgM and MHCⅡ mRNA levels were relatively greater for the spleen and head kidney indicating the importance and central position of systemic immunity. Expression levels were also high for the gills while skin levels were the lowest. IgM and MHCⅡ mRNA levels were altered over time following vaccination and the hindgut, liver and spleen were similar indicating a close relationship, so the The absolute value of r is used to analyze the correlation among different organs immunized. It can be inferred the existence of an internal immune molecular mechanism for Immune synergy hindgut-liver-spleen, from the peak time(14th d), the relative ratio of genes expression in the same tissues between the immunized grouper and the control group(26 times), and Pearson correlation coefficient( 0.8<|r|<1). Injection challenges with live V. harveyi indicated that the relative protection rates for the Crucian carp and Grouper was basically the same at 44.4 and 47.4 %, respectively .It is believe that crucian carp may be used as a substitute for the valuable grouper in immunity experiment, just from aspect of the relativepercent survival(RPS) and how it changes with time .But they were not consistent about the IgM mRNA expression between that of crucian carp and grouper after immersion the Vibrio vaccine.